Collecting and Directing the Correct Qur’anic Readings in Tafsir Al-Baydawi (658 AH) in Surat Al-Qadr (Islamic Sciences Journal, 2024)
The research addresses the topic of “Guiding Readings in Tafsir al-Baydawi: A Study on Its Importance in Understanding the Qur’an.” The research highlights the importance of the science of readings and Tafsir al-Baydawi and their influence in guiding concepts of the Glorious Qur’an. Further, the research addresses the role of Al-Baydawi as a multidisciplinary scholar in the Sharia sciences and highlights the focus on directing readings and their importance in extrapolating Qur’anic connotations.It should be noted that Al-Baidawi did not limit himself to the frequent readings only, but also discussed irregular readings. The research discusses the importance of directing the readings and their role in understanding the purposes of the verses and the concepts of the Glorious Qur’an, and this is highlighted through Al-Baydawi’s manifestations of the various readings.The research shows its results that confirm Al-Baydawi’s distinction as a distinguished and knowledgeable scholar and thinker in the Islamic sciences. In conclusion, it is summarized that the results of the research and emphasizes the importance of guiding the readings in Al-Baydawi’s interpretation, and refers to the Meccan surah “Al-Qadr” as an example of the different readings and their interpretation.
Keywords: Interpretation of Al-Baydawi, correct readings, guidance of readings, interpretation of the Qur’an, Surat Al-Qadr.